Protest music in Chile: Vehicle for diffusion of the social consignment of natural law - Vázquez Martínez, Luis; Aguado Romero, Gabriela (DIXI, 2021)
Objective: To demonstrate that natural rights, as they are inherent to the conscience, are claimed by citizens through different mechanisms, one of which is social music, since it allows the values ​​and principles that are required to be easily spread. Methodology: The analytical and historical methods were used because the parts of a social problem were analyzed and thus the causes were observed, which were pursued to their origin. Results: Individuals will always fight to safeguard their natural rights since they are not willing to lose them with arguments emanating from governments established in illegality or lack of legitimacy. Conclusions: A government may have a margin of maneuver if it has legitimacy; otherwise, the same society will fight to change that situation that generates disadvantage for its members. In fact, it will use all the means at its disposal to achieve this, for which the dissemination of the message becomes important and in many cases this will be done through social music.